2019
DOI: 10.1037/spq0000283
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the parent role in school-based interventions for autism: A systematic literature review.

Abstract: Parent-focused intervention for children with autism spectrum disorder (ASD) has garnered considerable evidence of effectiveness for treating core symptoms of the disorder. However, these programs often teach parents discrete skills that may or may not align with school-based interventions. Family–school partnerships (FSPs) are essential for children with ASD given the complex presentation of symptoms characteristic of this disorder. It is unclear how and to what degree current school-based interventions for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…For caregiver behavioral change to occur in VF, it is important that families buy into the utility of the video recording and review ( 1 ), as they did in the present study. Our VF intervention allowed for the inclusion of caregivers not just as passive recipients of intervention, but also in the roles of intervention collaborator and agent of the intervention ( 49 ), promoting caregiver buy-in to the intervention. In addition, caregivers in the NDBI+VF group reported increased insight into their own interactive strategy implementation because they reported that VF helped “to understand how we can play with our kids,” and “to find my shortcomings,” consistent with reflections of caregivers who received VF in past studies ( 23 , 27 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…For caregiver behavioral change to occur in VF, it is important that families buy into the utility of the video recording and review ( 1 ), as they did in the present study. Our VF intervention allowed for the inclusion of caregivers not just as passive recipients of intervention, but also in the roles of intervention collaborator and agent of the intervention ( 49 ), promoting caregiver buy-in to the intervention. In addition, caregivers in the NDBI+VF group reported increased insight into their own interactive strategy implementation because they reported that VF helped “to understand how we can play with our kids,” and “to find my shortcomings,” consistent with reflections of caregivers who received VF in past studies ( 23 , 27 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the prevalence of autism among school-age children and the high occurrence of comorbid behavior, emotional, and medical issues, autistic children may benefit from supportive school environments that bolster parent-teacher relationship quality and family involvement (Shahidullah et al, 2020). However, research examining parent-teacher relationship quality and family involvement among families of autistic students is limited (Rispoli et al, 2019). Rispoli et al (2019) specifically noted the need for additional research that can inform the development of family-school interventions for autistic children.…”
Section: The Present Studymentioning
confidence: 99%
“…However, research examining parent-teacher relationship quality and family involvement among families of autistic students is limited (Rispoli et al, 2019). Rispoli et al (2019) specifically noted the need for additional research that can inform the development of family-school interventions for autistic children. Intervention development requires the careful study of contextual factors that are proximal to adoption, implementation and maintenance, positioning child behavioral and physical health, and parent mental health as primary targets (Meyers et al, 2012).…”
Section: The Present Studymentioning
confidence: 99%
“…Teachers of all students, but even more importantly, teachers of students with special learning needs/disabilities, must also be comfortable working with the parents of their students, and strong parent-school partnerships are critical in facilitating this expectation [3,[5][6][7]. According to a 2015 report from the United States Department of Education [8], the majority of the parents surveyed participated in a school-related activity, including parent-teacher conferences, school/class events, volunteering, and/or fundraising.…”
Section: Introductionmentioning
confidence: 99%